DIFFERENCES IN PHYSICAL ACTIVITY OF ADOLESCENTS OF DIFFERENT SEXES BETWEEN 12 AND 15 YEARS OLD ON DIFFERENT DAYS OF WEEK - Štemberger, Vesna; Petrušič, Tanja (Sport - nauka i praksa, 2023)
Achieving the recommended daily level of physical activity (PA) in adolescent boys and girls helps improve their cardiovascular health, maintain a healthy body weight, and promote mental health. The purpose of our study was to determine whether there were statistically significant differences between boys and girls aged 12 to 15 years with respect to age and amount of PA on different days of the week. The sample included 606 7th, 8th, and 9th grade students from four Slovenian elementary schools who participated in the study by completing a questionnaire (IPAQ; International Physical Activity Questionnaire, 2006). We used a quantitative research approach and the method was causal-non-experimental. The Shapiro-Wilk test was used to determine whether the data were normally distributed at a statistically significant level of risk (p > 0.05). Because of the non-normal distribution of the variables (p < 0.001), the non-parametric Mann-Whitney test was used to determine statistically significant differences between genders, and the Kruskal-Wallis test was used to determine statistically significant differences between age groups. Boys were statistically significantly more active than girls on all days of the week except Wednesday (Mon.: p=0.018; Tues.: p=0.001; Thurs.: p=0.020; Fri.: p=0.015, Sat.: p=0.012; Sun.: p=0.001). Significant differences in PA levels between seventh-, eighth-, and ninth- graders occurred only on Sundays (p
Keywords: boys; girls; physical activity; sport